Answers

2015-05-14T17:46:41+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
3w+9=3(2w+3) \\\\ 3w+9=6w+9 \\\\ 3w-6w=9-9 \\\\ -3w=0 \\\\ \boxed{w=0}
0
w=0 so we replace w with 0 in 3w+9=3(2w+3) and we have:
3 * 0 + 9= 3( 2 * 0 + 3)
0 + 9 = 3( 0+3)
9= 3*3
9=9 so it's checked ;)
2015-05-18T14:56:59+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
3w+9=3(2w+3)
Distribute first
3w+9=6w+9
Subtract both sides by 3w
9=3w+9
Subtract both sides by 9
3w=0
Divide both sides by 3
w=0
Hope this helps =)
0